Hubungan Tingkat Pengetahuan Kelompok Pemuda dengan Efikasi Diri dalam Pertolongan Pertama Kecelakaan Lalu Lintas - Latifah Siregar; Nabilah Siregar; Julianto Julianto; Yohanna Adelina Pasaribu (Pelantar Press, 2025)
Appropriate first aid is expected to be carried out by the person who first finds an emergency event in this case a traffic accident to reduce mortality, prevent further complications, and accelerate healing in victims. The study aims to determine the relationship between the level of knowledge of youth groups and self-efficacy in first aid for traffic accidents. This study is an observational analytical study using a cross-sectional approach, conducted in the Huta III village Simalungun Regency on 50 samples. Data analysis using the Chi square test. The results of the analysis can be concluded that some respondents as many as 25 people (50%) have insufficient knowledge about first aid for traffic accidents, the majority of respondents as many as 29 people (58%) have low self-efficacy about first aid for traffic accidents, and there is a significant relationship between the level of knowledge and self-efficacy in first aid for traffic accidents (p value = 0.000). It is hoped that education or training for the community, especially youth groups, regarding first aid for traffic accidents in order to increase knowledge and self-efficacy in providing first aid.